How to relieve teething syndrome in babies - D. V. Kovalev; I. V. Kovaleva (Лечащий Врач, 2021)
Teething is a natural physiological process. It is very important that it passes without complications that can lead to improper formation of permanent teeth, malocclusion, infections, etc. According to statistics, only 30% of babies tolerate such moments more or less calmly, and 70% of children experience the so-called teething syndrome (in accordance with ICD-10 is coded as K00.7), which is accompanied by a number of nonspecific symptoms – fever, child anxiety, sleep and appetite disturbances, runny nose, cough, vomiting, regurgitation, loose stools. Because the symptoms are nonspecific, teething syndrome is always a syndrome of exclusion. The pediatrician must make sure that the child does not have ARVI, acute intestinal infection and a number of other pathological conditions, up to such serious ones as pneumonia, pyelonephritis and acute meningitis. When the doctor is confident that the existing symptoms are directly related to teething, the first step is to reduce the pain in the sore gums. After all, it is pain that causes crying, sleep disturbances, poor appetite and other complaints that reduce the quality of life for both the baby and his parents. If the pain and discomfort associated with teething cannot be relieved by non-drug methods, drug therapy may be needed, in particular, the use of a dental gel with lidocaine and cetylpyridinium chloride, which has an analgesic effect and mild antiseptic properties.